(untitled) (INNOVATIVE ECONOMY, 2020)
Herasymenko H.V. REMOTE EMPLOYMENT AS A PHENOMENON OF SOCIAL AND LABOR RELATIONS Purpose. The aim of the article is working out of institutional norms of distance employment in the context of social and labor relations. Research of methodology. The theoretical and methodological basis of the research is the position of modern economic science, as well as scientific works of domestic and foreign scientists on the issues of regulation of social and labor relations in the context of the formation of the information economy. To achieve this goals, an interdisciplinary approach is used that allowed the actual organizational and economic issues of regulation of social and labor relations of non-standard employment to be substantiated in the normative and legal format. Generalization of the scientific work and comparative analysis of the provisions of the draft Labor Code of Ukraine, which made it possible to make proposals for supplementing labor norms in the part of distance employment conducted by the normative legal basis of the study are the Conventions of the International Labor Organization, the legislation of Ukraine, the draft Labor Code of Ukraine to develop innovations in the institutional context of the organization of work as a factor in improving the efficiency of human resources management of enterprises. Findings. According to the results of the analysis, the concept of “distance employment” in the scientific format and the legal field provides an author’s interpretation of distance employment, the status of a remote worker is substantiated, the features of the worker’s place of work of a remote worker are determined, as well as suggestions on the content of the employment contract (agreement) in remote mode, which will prevent risks and threats to the parties of social and labor relations in the process of remote work. Originality. The proposals on the introduction of institutional tools for regulating distance employment in the social and labor format in addition to the modern practice of the use of civil and law contracts are substantiated. Unlike the existing scientific developments and institutional regulation of distance employment on the basis of civil law, the author’s proposals are aimed at introducing a social and labor format for coordinating the interaction between the employer and the hired employee while performing the work in remote mode. Practical value. The treatment of distance employment that was given by the author, the status of a remote worker, the workplace of a remote worker, as well as proposals on obligatory provisions of the employment contract in general and the conditions of work in the remote mode in particular, can be used in updating and improving the institutional environment for regulating social and labor relations of non-standard employment. Key words: social and labor relations of employment; distance employment; remote work mode; distance worker; work place of a remote worker; institutional regulation of distance employment.